Hinduizm wedyjski i chrześcijaństwo – bliźniaczo różne myśli religijno-filozoficzne. (W hołdzie pani Profesor Joannie Sachse!) - Byrski, Maria Krzysztof (Instytut Studiów Klasycznych, Śródziemnomorskich i Orientalnych UWr, 2018)
Meeting of civilizations is a fact that implies give and take attitude. Since religions constitute an essential component of civilizations, it is a must for them too, to meet not in the spirit of confrontation and conversion but precisely in the spirit of give and take which stems from the mutual respect and recognition of the fact that all religions are a dramatic effort of humanity to discover and describe the sense of existence. The title of this essay – „Vedic Hinduism and Christianity – the twins unlike religious and philosophical thoughts” – purposefully invokes an oxymoron to underline at the same time similarity and difference of these two thoughts endeavours. The inquisitive study of one of the most important religious texts of ancient India – the Purushasukta hymn of Rigveda, which formulates the cosmogonical doctrine of the self – immolation of the Person (Purusha),conducted from the point of view of cultural Christian, is an attempt to show its complementary character vis a vis the doctrine of Christ sacrifice. In consequence the nature of the last one stands a chance to be reinterpreted – not contrary to the Christian scriptures – as the repetition in time and space of the creative sacrifice of God the Father at the beginning of time and space, while God the Father we equate with Purusha of the Vedas
Keywords: Person – Lord of Creatures (Purusha – Prajapati); Hymn Person (Purusha-Sukta); Yehoshua; Prosn; sacrifice; Cultured Christian; Sayana; belivers; specialists in religious studies